Hubungan Volatilitas Harga Konsumsi Beras Terhadap Ketahanan Pangan di Jawa Timur - Aulia, Anisa Nurina; Wardhana, Danu Indra; Afifutoyyiba, Muhhammad; Pamungkas, Teguh Putra (Universitas Galuh, 2025)
Food security policies have been established covering aspects of food availability, distribution and price stability, food access, and supporting policies. Stable food prices are generally also desired by the public because highly fluctuating prices have implications for the risks and uncertainties that must be faced in making decisions when prices fluctuate beyond the normal limits of price stabilisation, so the Government immediately intervenes, for example when price increases occur in rice commodities. Food price volatility will have a long-term impact on producer income and disrupt commodity trading activities and will make strategic commodity price fluctuations that occur causing food commodity market players, both producers and consumers, to experience difficulties in carrying out economic activities. Therefore, a risk analysis of food commodity prices is needed so that price fluctuations can be resolved immediately. Domestic prices fluctuate so much that this research is important to do to determine the volatility of the retail price of rice as the main food in East Java. Based on ARCH / GACRH analysis, the best model for rice price volatility at the consumption level is ARIMA (1,1) - GARCH (1,0), the volatility value obtained is 0.53 which is included in the low volatility level. While the relationship between rice price volatility and average weekly consumption per capita which illustrates the level of food security is 0.940, so there is a close relationship. So that the government is obliged to make policies so that rice prices remain stable at the consumer level, so that there are no price spikes that will affect food security.